Improving Heart Failure Readmission Costs and Outcomes With a Hospital-to-Home Readmission Intervention Program. (March 2019) - Bilchick, Kenneth; Moss, Travis; Welch, Timothy; Levy, Wayne; Stukenborg, George; Lawlor, Bryan T.; Reigle, Juanita; Thomas, S. Craig; Brady, Carolyn; Bergin, James D.; Kennedy, Jamie L. W.; Abuannadi, Mohammed; et al.
A retrospective cohort study was performed of the Hospital-to-Home (H2H) program, a rapid clinic follow-up program for patients with recent heart failure (HF) admissions at the University of Virginia Health System. There were 6761 hospitalizations among 4685 patients (age 67.5 ± 14.2 years, 43.9% female), and 759 had H2H follow-up. Thirty day mortality after the initial HF hospitalization was lower in H2H patients (1.84% vs 3.13%; P = .049), and this difference remained significant after adjustment in a multivariable logistic regression model (odds ratio = 0.56 [95% CI = 0.31-099]; P = .046). There also was a 24% reduction in readmission days within the first 30 days after the index admission ( P < .0001), and readmission cost savings were found to be greater than the costs of staffing the H2H clinic. In summary, the H2H program is cost-effective, with significant improvements in survival, readmission days, and readmission costs over 30 days.